2013
DOI: 10.1063/1.4796000
|View full text |Cite
|
Sign up to set email alerts
|

Potential model for the bottomonium

Abstract: We use a Euclidean propagator obtained from lattice simulations in Landau gauge to arrive at a potential model for the bottomonium. Following this non-relativistic approach, we then find the spectrum of the bottomonium numerically and compare it with the spectrum obtained using a Coulomb plus linear potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Theoretically, the quarkonium system has been thoroughly studied with potential models, [19][20][21][22][23][24][25] effective field theory approaches, 26,27 and lattice gauge theory calculations. 28,29 Large Hadron Collider (LHC) 30 with higher energy and intensity. The center-ofmass energy of the proton-proton (pp) collisions reached 13 TeV in 2015, which is about 7 times higher than that attained at the Tevatron (pp).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the quarkonium system has been thoroughly studied with potential models, [19][20][21][22][23][24][25] effective field theory approaches, 26,27 and lattice gauge theory calculations. 28,29 Large Hadron Collider (LHC) 30 with higher energy and intensity. The center-ofmass energy of the proton-proton (pp) collisions reached 13 TeV in 2015, which is about 7 times higher than that attained at the Tevatron (pp).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this method are presented in Section 4 and we present our conclusions in Section 5. Preliminary results of our study were reported in [9].…”
Section: Introductionmentioning
confidence: 76%
“…Lastly, in order to convert the propagator in Eq. (21), which was obtained in Euclidean space, to Minkowski space, we undo the Wick rotation, taking δ µν → −g µν . We obtain 3…”
Section: Potential From Lattice Propagatormentioning
confidence: 99%